An overview of the current analytical methods for halal testing - Jaswir, Irwandi; Mirghani, Mohamed Elwathig Saeed; Mohd. Salleh, Hamzah; Ramli, Noriah; Octavianti, Fitri; Hendri, Ridar (Springer, 2016)
The objective of this paper is to review all the methods that have been developed in the authentication of halal food products, including those developed in our institute. The need for proper control and monitoring of authenticity of food is a serious matter to the authority and the food manufacturers. Strong commitment and continuous support from the government through various agencies would ensure the integrity of the food itself, in terms of both safety and quality. Islamic food laws are based on cleanliness, sanitation, and purity. Hence, the importance of establishing laboratories and using analytical techniques (methods) of authenticity in food for ensuring food safety and protecting consumers from fraud and deception as well as for product recall purposes. Laboratory data may help define the overall scope of work, levels of worker protection, and remediation and disposal methods. Instrumental methods in detection of contamination and/or adulterants in food would clarify any doubt to Muslims, and information can be disseminated for consumer transparency giving better trust and confidence to the authority.